Pelatihan tenaga kesehatan dalam penegakan diagnosis penyakit menular seksual dengan pemeriksaan mikroskopis sederhana di fasilitas kesehatan primer - Rivani, Erizka; Nurwany, Raissa; Oktharina, Eka Handayani (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Sexually transmitted diseases (STDs) encompass a range of infectious diseases that can be attributed to parasites, bacteria, viruses, or fungi. Inaccurate diagnosis can lead to ineffective treatment and increase transmission rates. Furthermore, in an era of widespread antimicrobial resistance, it is imprudent to administer empirical antimicrobial treatment without revelation of potential etiology information which could leads to suboptimal clinical outcomes. Patients suffering from STDs frequently seek initial assistance at primary healthcare facilities, such as community health centres. Enhancing the understanding of health professionals regarding the current state of STDs, including proper diagnostic techniques, will contribute to the improvement of health services. A simple test that can be performed is a microscopic examination of specimens containing genital secretions. The accuracy of microbiological examination heavily relies on the quality of the specimen. Providing training to general practitioners, nurses, midwives, and laboratory personel on specimen collecting techniques and microscopic examination techniques is needed to enhance the precision of diagnosis. The training involved both presentations and hands-on experience in collecting specimens for microscopic examination, as well as techniques for simple microscopic examinations to confirm the etiological diagnosis of STDs. An increase in the trainees' understanding was evident after the training, as reflected in the rise in the average post-test score compared to the pre-test score. Health workers have also been able to independently practice specimen collection techniques and conduct microscopic examinations after attending the training. This training has improved health workers' proficiency in managing STDs and contributed to a higher diagnosis coverage rate.